Towards a mechanistic understanding of fish species niche divergence along a river continuum - Troia, Matthew J.; Gido, Keith B. (My University, 2014)
Environmental niche modeling is a valuable tool but it often fails to identify causal links between environmental gradients and individual- or population-level performance that drive species' distributions. Correlation between the abundances of stream fish species and longitudinal position in stream networks is well documented and is hypothesized to occur through differential environmental filtering of trophic traits. Still, trophically similar congeners often exhibit complementary distributions along stream size gradients, suggesting that other mechanisms are important. We present niche models to test the hypothesis that four congeneric pairs (Teleostei: Cyprinidae) exhibit complementary distributions along a gradient of stream size in the central Great Plains of Kansas, USA. Stream size was the strongest predictor of abundance compared to five other environmental variables tested and three of the four species pairs exhibited complementary distributions along a stream size gradient. We carried out field experiments to quantify potentially causal environmental gradients (food resources, temperature, and turbidity) and four measures of individual performance (adult spawning success and juvenile survival, condition, and growth) along a stream size gradient for one congeneric pair: Pimephales notatus, a tributary species and P. vigilax, a river mainstem species. These experiments revealed an increase in temperature and food resources with stream size, along with a corresponding increase in adult spawning success, juvenile condition, and juvenile growth for both species. We conclude that these congeners respond similarly to abiotic gradients associated with the river continuum and that complementary distributions are a consequence of biotic interactions, differential environmental filtering evident in an unmeasured performance metric, or differential environmental filtering by a direct environmental gradient operating at longer timescales.
Citation: Troia, M. J., & Gido, K. B. (2014). Towards a mechanistic understanding of fish species niche divergence along a river continuum. Ecosphere, 5(4), art41. https://doi.org/10.1890/ES13-00399.1
Keywords: Congeners; Cyprinidae; Environmental niche modeling; Great Plains; Individual performance; Mechanistic niche modeling